Research Involvement and Gender Disparities Among Pediatric Surgeons: A Multinational Survey - Santiago-Martínez, Saioa; Aziz, Dayang Anita Abdul; Bjørland, Kristin; Correa, Catalina; Gagilyte, Ruta; Ellul, Sarah; Hernández, Esperanza; Arribas, Paula Jimenez; Lindert, Judith; Nah, Shireen Anne; Pos, Lucie; Reusens, Helena; Schmedding, Andrea; Sharma, Shilpa; Stefanescu, Maria-Christina; Souhem, Touabti; Vasconcelos-Castro, Sofia; Vercauteren, Charlotte; Bisimwa, Wani Alliance; Zaman, Azrina (European Journal of Pediatric Surgery, 2025)
There is a lack of background regarding knowledge about the involvement of pediatric surgeons (PSs) in scientific activities. We aimed to investigate scientific activity among PSs worldwide.An anonymous online questionnaire in English collected demographic data, time spent on research, participation in scientific conferences, publications, and funding for conference attendance. Co-authors distributed it through national and international pediatric surgery societies and groups to reach their members.A total of 526 PSs responded (57% female). About 55% of those surveyed reside in Europe. Most worked in university hospitals (61%), 9% at a university faculty, and 0.8% in a research facility. Only 23% were engaged in research, with similar rates for females (21%) and males (26%) (NS).Additional time out of working hours was required for research, particularly among female PSs. Full compensation for research was reported by 10% of females and 29% of males (p < 0.02). Around 73% had attended at least one local, regional, national, or international scientific conference (75% of females vs. 70% of males, NS), while 84% had no funding for at least one event (87% of females vs. 80% of males, NS). Scientific paper was presented by 69% at some conference. At least one scientific paper was published by 20% (17% of females vs. 23% of males, NS).Research involvement among PSs is limited, with unpaid work and funding gaps, particularly among women. Potential solutions include improving research training, structured mentorship (especially for women), institutional support for protected research time, and equitable access to funding opportunities.
Keywords: pediatric surgery; survey; research opportunities; equality; gender bias